THE IMPACT OF REGIONAL MINIMUM WAGE, ECONOMIC GROWTH, MEANS YEARS OF SCHOOL, AND COVID-19 PANDEMIC ON BANTEN’S OPEN UNEMPLOYMENT RATE 2017-2022 - Arisudana Yoga Pramana; Rumayya Rumayya (SEAN Institute, 2023)
Unemployment in Banten Province become a crucial issue because the needs to fullfill Sustainable Development Goals (SDGs) to alleviate the unemployment and the high rate of Banten’s unemployment. The purpose of this study was to determine the significancy of regional minimum wage, economic growth, years of schools, and COVID-19 impacts to open unemployment rate in Banten 2017-2022. This research wiil be analyzed using panel data regression method. The data in this study are secondary data. Hypothesis testing that will be conducted is the linearity test or R-squared, simultaeous significancy test, and partial significancy test. The significance variables that affect the open unemployment rate in Banten are economic growth, means years of school, and COVID-19. We suggest that governement must have government fund aid, remote working, and remote schooling to decrease the impact of future pandemic-like crisis.